PENGEMBANGAN PROTOTYPE BALL THROWING DIGITAL DENGAN VISUAL LIGHT SYSTEM SEBAGAI MEDIA LATIHAN UNTUK PENJAGA GAWANG PADA CABANG OLAHRAGA SEPAK BOLA - Muhammad Zakiy Muflih, - (2020)
This study aims to see how the physical model, shape and type of digital throwing ball prototype with a visual light system as a training medium for goalkeepers in soccer. This research is a qualitative study using research and development (R&D) methods. The sample used in this study were 2 goalkeepers of UPI Soccer UKM. The instruments used are expert testers in the field of sports and measurement tests, whole-body reactions and futsal ball throwers. The result of this research is the creation of a digital ball throwing prototype with a visual light system as a training medium for goalkeepers in soccer. With the existence of a digital throwing ball prototype with a visual light system as a training medium for goalkeepers in this sport, it can help coaches and athletes in a variety of training for goalkeepers in soccer. The digital ball throwing prototype with a visual light system as a training medium for goalkeepers in soccer has sufficient validity for reaction time (rcount = 0.417, 0.40≤rcount≤0.59) and high validity for speed (rcount = 0.603, 0.60≤ rhitung≤0.79). The digital ball throwing prototype with a visual light system as a training medium for goalkeepers in soccer has sufficient reliability value for reaction time (r = 0.464, 0.40-0.59), and high reliability for speed (r = 0.679, 0.60- 0.79).